A method for concealment of displayed data - (:unkn) unknown (ELSEVIER SCIENCE BV, 2003)
A concealment method is proposed to prevent the displayed images and texts from being seen by onlookers, while letting the authorized user see the full dynamic content. The concealment method is based on sequentially displaying the dataframe and a compensating inverse dataframe. The eye cannot discern the two frames and can only see a gray screen or a public image. The authorized user wearing LCD shutter glasses, on the other hand, can see the regular data frame. An optimum inverse data frame construction is achieved. Furthermore, the real time computation problem is solved, which makes the proposed method practically applicable to most PC systems. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: data privacy; inverse image; shutter glasses